2012
DOI: 10.1111/j.1524-4741.2012.01228.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Prognostic Factors in Patients with Carcinomatous Meningitis Secondary to Breast Cancer

Abstract: Prognosis in patients with carcinomatous meningitis (CM) is poor, and numerous prognostic factors for response and survival have been described, but remain controversial. In general, series are small and involve a heterogeneous type of solid neoplasms. The purpose of this study was to describe a series of patients with breast cancer-associated CM to determine the clinical features and prognostic factors associated with survival. We conducted a retrospective study on 49 patients diagnosed between January 2003 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
35
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 48 publications
7
35
0
Order By: Relevance
“…16,19,20 Of these, headache is the most common among all 3 anatomical areas of the CNS. 16,19,20 These symptoms are attributed to high intracranial pressure and may be associated with papilledema. Headaches are often described as worse when awakening or lying down and can interfere with sleep.…”
Section: Pathogenesis Of Symptomsmentioning
confidence: 99%
See 4 more Smart Citations
“…16,19,20 Of these, headache is the most common among all 3 anatomical areas of the CNS. 16,19,20 These symptoms are attributed to high intracranial pressure and may be associated with papilledema. Headaches are often described as worse when awakening or lying down and can interfere with sleep.…”
Section: Pathogenesis Of Symptomsmentioning
confidence: 99%
“…In a study of leptomeningeal metastases from breast cancer and a study of neoplastic meningitis due to several different primary tumors, researchers found that the median Karnofsky performance status was approximately 70%. 8,16 …”
Section: Physical Examinationmentioning
confidence: 99%
See 3 more Smart Citations